Isokinetic evaluation of knee muscles in soccer players: discriminant analysis - Mazuquin,Bruno Fles (2015)
ABSTRACT Introduction: Muscle activity in soccer players can be measured by isokinetic dynamometer, which is a reliable tool for assessing human performance. Objectives: To perform isokinetic analyses and to determine which variables differentiate the under-17 (U17) soccer category from the professional (PRO). Methods: Thirty four players were assessed (n=17 for each category). The isokinetic variables used for the knee extension-flexion analysis were: peak torque (Nm), total work (J), average power (W), angle of peak torque (deg.), agonist/ antagonist ratio (%), measured for three velocities (60°/s, 120°/s and 300°/s), with each series containing five repetitions. Three Wilks' Lambda discriminant analyses were performed, to identify which variables were more significant for the definition of each of the categories. Results: The discriminative variables at 60°/s in the PRO category were: extension peak torque, flexion total work, extension average power and agonist/antagonist ratio; and for the U17s were: extension total work, flexion peak torque and flexion average power. At 120°/s for the PRO category the discriminant variables were: flexion peak torque and extension average power; for the U17s they were: extension total work and flexion average power. Finally at 300°/s, the variables found in the PRO and U17 categories respectively were: extension average power and extension total work. Conclusion: Isokinetic variables for flexion and extension knee muscles were able to significantly discriminate between PRO and U17 soccer players.